A170 MACROPHAGE SUBSET PHENOTYPE IS ALTERED IN CHRONIC HCV INFECTION & MAY CONTRIBUTE TO GENERALIZED CD8+T-CELL DYSFUNCTION. (1st March 2018) - Ahmed, F; Kumar, A; Cooper, C; Crawley, A M
Abstract: Background: It has been previously shown that chronic HCV infection causes generalized CD8+T-cell impairment, not limited to HCV-specific CD8+T-cell populations. In such an inflammatory hepatic disease, infiltrating monocyte-derived macrophages (MDM) contribute to a micro-environment that could influence cells trafficking through the liver, including CD8+T-cells. These MDM can differentiate into M1 (classically-activated) and M2a, M2b, M2c (alternatively-activated) with pro- and anti-inflammatory functions, respectively. Whether MDM subset generation in chronic HCV infection is altered in the liver is unknown. Furthermore, how these subsets influence CD8+ T-cell function needs investigation. We hypothesize that MDM subset phenotypes are altered in chronic HCV infection, thereby contributing to CD8+T-cell dysfunction. Aims: Aim 1: Assess the phenotypic differences between macrophage subsets in health and chronic HCV infection. Aim 2: Examine the role of polarized macrophage subsets in altering CD8+T-cell function. Methods: MDM subsets were generated from blood collected from healthy controls and HCV-infected individuals. Phenotypes were confirmed using surface receptors (CD163, CD206 and CD86) and quantification of secreted cytokines (IL-6, IL-10, IL-12, IFN-y and TNF-α). Autologous co-culture of MDM subsets and isolated CD8 + T-cells in health enabled the assessment of CD8 + T-cell functions. Results: MDM subset phenotyping in chronic HCV infection suggests M2a cells have a higher percentage of CD206 + than M0 subset whereas in health, they showed no significant difference. In HCV infection, the concentration of IL-6 in M2a subset supernatants was significantly higher than healthy controls. In chronic infection, TNF-α release by any MDM subset was undetectable, whereas in health, M1 cells produced significantly higher amounts of TNF-α compared to M0 and M2a subsets. No differences were observed in the concentration of IL-10, IL-12p70, IFN-y, CD86 and CD163 between the subject groups. In uninfected controls, co-culturing CD8 + T-cells with M1 macrophages significantly increased the percentage of perforin +, CD107a + and IFN-y + CD8 + T-cells, compared to CD8 + T-cells alone and M2a subset. Conclusions: Phenotypic alterations in health and chronic HCV infection are evident both in terms of surface receptors and secreted cytokines suggesting impairment of MDM subsets. The importance of an M1 phenotype, in being able to prime CD8 + T-cells and induce perforin and CD107a is evident. How the altered phenotype of MDM subsets in chronic HCV infection will influence the CD8 + T-cell function, needs to be further investigated. Funding Agencies: Canadian Network on Hepatitis C (Stipend Funding), NSERC (Lab Funding), OHTN, J.P.Bickell Foundation.